The best lawyer in a one-lawyer town : a memoir - Bumpers, Dale (University of Arkansas Press, 2004)
If Frank McCourt had grown up in Depression-era Arkansas, he might write like Dale Bumpers, one of the most colorful, entertaining, and wise politicians in recent American history, Atticus Finch with a sense of humor. In The Best Lawyer in a One-Lawyer Town, Bumpers tells the story of his remarkable journey from poverty to political legend, and the result is a great American memoir that has attracted wide acclaim for its clever southern charm.
Keywords: Bumpers, Dale.; United States. -- Congress. -- Senate -- Biography.; États-Unis. -- Congress. -- Senate -- Biographies.; Bumpers, Dale; United States. -- Congress. -- Senate; Legislators -- United States -- Biography.; Governors -- Arkansas -- Biography.; Lawyers -- Arkansas -- Biography.; Arkansas -- Politics and government -- 1951-; Parlementaires -- États-Unis -- Biographies.; Gouverneurs -- Arkansas -- Biographies.; Arkansas -- Politique et gouvernement -- 1951-; Lawyers & Judges.; Governors; Lawyers; Legislators; Politics and government; Arkansas; United States; Since 1951; Biographies